Tren Bidang Information Science Research dalam Jurnal pada Google Scholar (2019-2024) - Nugrahani, Hadaina; Helma Pritanaya; Hajja, Lubada De; Sanbreven, Mochammad Zheva Ayrtoon; Trishinta, Nabilah; Safii, Moh. (UPT Perpustakaan UIN Alauddin Makassar, 2025)
Information science has evolved from information management into a multidisciplinary approach that encompasses data management, analysis, and communication, driven by the rise of digital data and the need for effective information management strategies. This field helps address modern challenges, enabling data-driven decision-making and improved communication. This study employs statistical and mathematical methods to collect, analyze, and understand bibliographic data related to articles and journals. Researchers use VOSviewer to visualize and analyze bibliometric networks, including citation relationships, bibliographic coupling, co-citation, or author collaboration. The foundation of modern information theory was established by Claude Shannon and Alan Turing. An analysis of research trends in Information Science Research (ISR) indicates a decline in publications from 2019 to 2024, decreasing from 173 articles in 2019 to only 4 articles in 2024. Of a total of 500 articles, 93.20% were written collaboratively. The data suggest that research in ISR is closely related to scholarly writing in the field of Library and Information Science.